Fostering innovative behaviours through leadership and fairness: commitment and citizenship behaviours as successive mediators - Khaola, Phomane Peter (My University, 2018)
Research literature not only suggests that the effects of leadership and organisational justice (social factors) on innovative work behaviour (IWB) are equivocal, but also presents a variety of intervening factors between the focal constructs. Conspicuously missing in the list of mediating factors is organisational citizenship behaviour (OCB), the factor that can theoretically facilitate IWBs. Similarly, although both OCB and IWB are discretionary work behaviours, little is surprisingly known about the relationship between these two extra-role constructs. Drawing on literatures across various research domains, the aim of this study was to develop and test a model that links leadership and fairness to IWB through the successive mediating roles of affective commitment and OCB. The study was based on survey of a random sample of 300 employees selected from 652 employees from a public university, and a convenient sample of 159 employees from private and state-owned enterprises in Lesotho. The Statistical Package for Social Sciences (SPSS) and the Analysis of Moment Structures (AMOS version 24) were used to analyse data. Specifically, the study used factor analysis; correlation; analysis of variance (ANOVA); and structural equation modelling techniques to address the hypothesised relationships. To reinforce quantitative results, an open-ended question on OCB was analysed qualitatively to give insights into why OCBs may facilitate IWBs. The results suggest that the model that fitted data well is the one in which the effects of both leadership and organisational justice on IWBs were successively mediated by affective commitment and OCB. Because of its social and affiliation-oriented nature, this study submits and concludes that OCB is an effective mediating factor between social factors (leadership and justice) and IWBs. This study not only contributes to literature by presenting a new perspective on how social factors relate to IWBs, but also guides managers on appropriate interventions they can use to inspire employees to engage in affiliation-oriented and proactive OCBs.
A thesis submitted to the faculty of Commerce, Law and Management in fulfillment of the requirements for the Degree of Doctor of Philosophy in Management March 2018
Keywords: Customer behaviour; Employee empowerment--South Africa